1991
DOI: 10.1002/bjs.1800780719
|View full text |Cite
|
Sign up to set email alerts
|

Lymph node counts in the upper abdomen: Anatomical basis for lymphadenectomy in gastric cancer

Abstract: The number of regional lymph nodes was determined in sites relevant to lymphadenectomy in gastric cancer in 30 cadavers. Tissue was cleared by dissolving fatty tissue, thus making lymph nodes with a diameter of at least 1 mm visible. All lymph node stations indicated by the Japanese Research Society for Gastric Cancer were studied. In stations 1-11 (corresponding with R2 resection) an average of 27 nodes (range 17-44 nodes) was found, whereas stations 1-16 (corresponding with R3 resection) showed an average of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
74
2
5

Year Published

1993
1993
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(89 citation statements)
references
References 8 publications
8
74
2
5
Order By: Relevance
“…Simply put, the extent (D1, D2, D3) corresponds to removal of the first, second and third echelons of lymph nodes surrounding the stomach. Wagner and colleagues carried out a systematic study of the gastric lymph node basins in 30 cadavers and determined that median numbers of lymph nodes in each echelon (as defined by the Japanese Research Society for Gastric Cancer) were 17, 27 and 43, respectively [20]. This roughly corroborates with the lymph node yield following a D1, D2 and D3 lymphadenectomy.…”
Section: • Echelons and Lymph Node Yieldmentioning
confidence: 76%
“…Simply put, the extent (D1, D2, D3) corresponds to removal of the first, second and third echelons of lymph nodes surrounding the stomach. Wagner and colleagues carried out a systematic study of the gastric lymph node basins in 30 cadavers and determined that median numbers of lymph nodes in each echelon (as defined by the Japanese Research Society for Gastric Cancer) were 17, 27 and 43, respectively [20]. This roughly corroborates with the lymph node yield following a D1, D2 and D3 lymphadenectomy.…”
Section: • Echelons and Lymph Node Yieldmentioning
confidence: 76%
“…The surgical specimens and lymph nodes were examined by pathologists specializing in gastric cancer using the updated edition of the UICC/ AJCC TNM staging system, which was then converted to the seventh edition at the time of our analysis [9]. For the purposes of the present study, the patients were divided into three groups according to the number of lymph nodes retrieved: patients with 15 harvested lymph nodes (LN 15), patients with 16-25 harvested lymph nodes (LN [16][17][18][19][20][21][22][23][24][25], and patients with >25 harvested lymph nodes (LN >25). The lymph node ratio (LNR) was defined as the ratio between metastatic and examined lymph nodes.…”
Section: Methodsmentioning
confidence: 99%
“…A D3 lymphadenectomy is defined as resection of the N3 grouping [42], while a D4 lymphadenectomy includes the para-aortic nodes [58]. It is difficult to directly correlate the number of LNs assessed with the type of lymphadenectomy, but autopsy studies have shown that a mean of 15 nodes can be harvested from a D1 lymphadenectomy, 17-44 nodes (mean ¼ 27) nodes from a D2 lymphadenectomy, and 25-64 (mean ¼ 43) from a D3 lymphadenectomy [59].…”
Section: Surgical Issues Of Lymph Node Dissection D1 Versus D2 Lymph mentioning
confidence: 99%